Strategic citizens of America: transnational inequalities and transformation of citizenship - Balta, Evren; Altan-Olcay, Ozlem (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2016)
This article analyses the process whereby 'natural' citizens of one country mobilize their resources so that their children receive by birthright, the citizenship of a rich liberal democracy. Utilizing the case of Turkish upper classes, who give birth in the USA in order to benefit from the jus soli principle, we trace the emergence of new inequalities at the intersection of multiple citizenship regimes. We show that, by mobilizing resources in markets of health care, travel, and real estate, those with means can acquire US citizenship for their children in expectation of future benefits. Because they are able to access 'valuable' citizenships, these actors can strategically combine privileges within nation states with inequalities between citizenship regimes at the global level for the children. Their differential access to citizenship enhances the gate-keeping functions of citizenship. Based on these observations, we draw an analogy between citizenship and property regimes, understood broadly.
Keywords: Citizenship; transnational citizenship; inequality; neoliberal citizenship globalization; new classes; Ethnic Studies; Sociology